Mature tree transplanting: Science supports best management practice. Issue 1 (2nd January 2016) - Pryor, Mathew; Watson, Gary
Abstract : Replicated research on transplanting mature trees (trunk diameter >750 mm) is not practical. Instead, we must apply the knowledge we have gained from studying smaller trees to maximise success at this larger scale. This article summarises our understanding of tree biology and horticulture contributing to the successful transplanting of trees, e.g. root loss and regrowth, water stress, carbohydrate status, root ball size, preparatory root and canopy pruning, timing of operations. The specific detail of the transplanting operations undertaken on four mature trees in Hong Kong in the last 15 years is then evaluated to examine the extent to which the arboricultural factors may have contributed to the outcome of each operation.